Immobilized inulinase on grafted alginate beads prepared by the one-step and the two-steps methods - Danial, E.; Elnashar, Magdy; Awad, G. (American Chemical Society, 2010)
Grafted alginate beads were prepared using the Encapsulator by two methods, the one-step and the two-step. The methods of grafting were characterized by thermal gravimetric analysis and infrared (IR). The lass transition (Tg) of both grafted gel beads showed gradual thermal improvement over the control gel. However, the one-step method showed higher Tg (231 °C) compared to the two-step method (220 °C). Both methods were also evaluated for immobilization of an important industrial enzyme, inulinase, to produce fructose, which is good for diet regimens and suitable for diabetics. The one-step method showed an enzyme loading capacity (ELC) of 530 U/g gel beads compared to 336 U/g gel beads for the two-step method. Accordingly, the one-step method has been chosen for further optimization. The ELC has been optimized to reach 1627 U/g gel using our locally prepared crude enzyme compared to 10.9 U/g by another author using purified inulinase. The immobilization process improved as did the enzyme's thermal stability, from 50 to 60 °C, which is the most suitable temperature used in food industries to prevent microbial contamination. The enzyme's thermal stability test at 60 °C and for an incubation time of 2 h, revealed a drastic decrease of the free enzyme activity to 21%, compared to 89% retention of activity for the immobilized enzyme. The immobilization process improved as well the enzyme's shelf stability, where the free enzyme lost all of its activity at room temperature after 28 days, the immobilized enzyme retained over 77% of its initial activity. These results are encouraging to produce high fructose syrup on the industrial scale as the carrier is efficient and the method is simple and economic.?©?2010 American Chemical Society.